Reduksi Miskonsepsi Mahasiswa pada Prinsip Kerja Kapasitor melalui Penerapan Simulasi PhET - Pratama, Defrianto (Universitas Negeri Surabaya, 2023)
This study aims to reduce the number of students who have misconceptions about the working principle of capacitors. PhET simulations are used in lectures to overcome these misconceptions. Diagnostic test results using the Four-Tier Test show that an average of 41.3% of students experience misconceptions about each of the concepts tested. However, after the PhET simulation-assisted lectures were held, the average number of students who had misconceptions decreased to 6.9%. The McNemar test shows that there is a significant change in the number of students who have misconceptions about each concept after attending the PhET simulation-assisted lectures. Thus, these results indicate that the application of PhET simulations in lectures is effective in reducing student misconceptions about the working principle of capacitors. Keywords: Misconceptions, PhET, Capacitors, Four-Tier Test, Virtual Laboratory.